Elevated IL-6 and TNF-α Associated with Treatment-Resistant Depression in Virally Suppressed HIV Patients: A Cross-Sectional Biomarker Study - Wisnu Wardhana Putra; Muhammad Yusuf; Mahmood Abbas; Nadia Khoirina; Felicia Sari; Abdullah Assagaf (Scientia Psychiatrica, 2025)
Introduction: Despite effective antiretroviral therapy (ART), major depressive disorder (MDD) remains highly prevalent in people living with HIV (PLWH). A subset of these patients develops treatment-resistant depression (TRD), creating a significant clinical burden. The "cytokine hypothesis" proposes that residual immune activation drives this resistance. This study aimed to evaluate whether serum interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) constitute a distinct biological signature of TRD, independent of viral load and smoking status. Methods: We conducted a cross-sectional case-control study (N=120) between January 2023 and June 2025. Participants were virally suppressed HIV-positive individuals stratified into three groups (n=40 each): (1) TRD (non-response > 2 antidepressants); (2) Treatment-responsive depression (T-Resp); and (3) Non-depressed controls (NDC). Smoking status (pack-years) was quantified. Cytokines were measured via high-sensitivity ELISA. Data were normalized using Log-10 transformation. We employed ANCOVA (adjusting for age, BMI, and smoking) and multivariate logistic regression to assess associations. Results: The TRD group exhibited significantly higher serum IL-6 and TNF-α compared to the T-Resp and NDC groups (p < 0.001). Although smoking prevalence was higher in the TRD group (45%), ANCOVA confirmed that depression status remained significantly associated with elevated cytokines after adjusting for smoking (F(2,116) = 42.5, p < 0.001). Logistic regression identified IL-6 as a robust correlate of TRD (Adjusted OR 2.15; 95% CI 1.45–3.18) with no multicollinearity (VIF=1.32). ROC analysis indicated high diagnostic accuracy for IL-6 (AUC=0.88). Conclusion: Elevated proinflammatory cytokines are strongly associated with TRD in PLWH, independent of viral replication and nicotine use. These findings support the potential utility of IL-6 as a stratification biomarker for immunomodulatory adjunctive therapies.